Forcing materialism upon metaphysics: Three approaches to Adorno's method. (30th October 2018) - Whyman, Tom
Abstract: Recent Adorno scholarship has been shaped by the idea that his critical theory cannot account coherently for its own method. Call this the Problem of Adornian Critical Theory (PACT). In this paper, I examine three recent approaches to Adorno—the "ethics of resistance" (associated with Gordon Finlayson and Brian O'Connor), "negative naturalism" (associated with Fabian Freyenhagen), and "inverse theology" (associated with Peter E. Gordon). Individually, I argue, all three approaches are subject to a key limitation that prevents them from being able to solve the PACT. But, by synthesising them, we can see how the scholarship already—effectively—possesses a solution to it. The synthesis that results is characterised in terms of "materialist metaphysics"—a position Adorno can clearly be read as articulating in the "Meditations on Metaphysics" chapter of Negative Dialectics.